Differences in Elderly Knowledge After Counseling on Bay Leaf Therapy to Reduce Hypertension Using Video in Ngapainia Village, North Konawe Regency - Ismawati Ismawati; Diah Indriastuti; Muhammad Syahwal (KLASICS, 2023)
Abstract. The elderly often experience various health problems due to the aging process. Problems that often occur in the elderly include hypertension, impaired uric acid levels, and cholesterol. Hypertension is the most common disease in the elderly, both due to organ changes due to the aging process and an unhealthy lifestyle. Health care for the elderly is advised to use herbs that have minimal side effects. This study aims to determine differences in the knowledge of the elderly after counseling on bay leaf therapy to reduce hypertension using video in Ngapainia Village, North Konawe Regency. This study uses a type of quantitative research with pre-experimental research methods, with a one-group pre-test post-test design approach. The sample of this study was 55 people aged> 60. Data analysis used the Wilcoxon test with significant criteria α (0.05). The results showed that before being given counseling on bay leaf therapy to reduce hypertension using video, the mean value was 5.1091 and the standard deviation was 1.65185. After being given counseling on bay leaf therapy to reduce hypertension using a video, the mean value was 8.0364 and the standard deviation was 1.66626. So the p-value is 0.000. That there is a difference in the knowledge of the elderly before and after being given bay leaf therapy counseling to reduce hypertension using video in Ngapainia Village, North Konawe Regency.